Simulação do ensaio ultrassônico pela técnica TOFD utilizando o método dos volumes finitos - Camurça, Paulo Jarbas (2014)
Nondestructive testing is widely used in industry to detect and size up discontinuities embedded in parts, equipments and structures. Numerical methods can be used to solve several engineering problems at lower costs and shorter times. In this perspective, this work aims to apply numerical modeling to simulate ultrasonic testing using the time of flight diffraction technique known as TOFD. For this, the two-dimensional wave equation was discretized by the finite volume method. Two algorithms (sequential and parallelized using of MPI library – Message Passing Interface) were developed to simulate the wave propagation. Three kinds of discontinuities (lack of penetration, porosity and crack) were embedded into the model material in order to investigate the interaction of the wave with discontinuities. Typical A-scan signals were obtained successfully to all studied conditions. Performance curves for the parallel version of the program were also obtained.